EDI3 links choline metabolism to integrin expression, cell adhesion and spreading - Lesjak, Michaela S (Cell Adh Migr, 2014)
Endometrial carcinoma differential 3 (EDI3) was the first member of the glycerophosphodiesterase (GDE) protein family shown to be associated with cancer. Our initial work demonstrated that endometrial and ovarian cancer patients with primary tumors overexpressing EDI3 had a higher risk of developing metastasis and decreased survival. Further analysis indicated that EDI3 cleaves glycerophosphocholine to choline and glycerol-3-phosphate, increases the levels of active PKC, and enhances the migratory activity of tumor cells. Despite these initial findings, EDI3 remained mainly uncharacterized. Therefore, to obtain an overview of processes in which EDI3 may be involved, gene array analysis was performed using MCF-7 breast cancer cells after EDI3 knockdown compared with a non-targeting control siRNA. Several biological motifs were altered, including an enrichment of genes involved in integrin-mediated signaling. More specifically, silencing of EDI3 in MCF-7 and OVCAR-3 cells was associated with reduced expression of the key receptor subunit integrin β1, leading to decreased cell attachment and spreading accompanied by delayed formation of cell protrusions. To confirm these results, we stably overexpressed EDI3 in MCF-7 cells which led to elevated integrin β1 expression associated with enhanced cell attachment and spreading - two processes critical for metastasis. In conclusion, our data provide further insight into the role of EDI3 during cancer progression.